The Role of Branched-Chain Amino Acid (BCAA) Supplementation in Sarcopenia among the Elderly - Rahaliya Salsabila Fatahuddin; Niam, Syaifun (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Sarcopenia is a syndrome characterized by loss of skeletal muscle mass, strength, and skeletal muscle function that occurs as a result of aging. To maintain muscle mass, a dynamic balance is needed between muscle protein synthesis (MPS) and its breakdown. BCAAs, including leucine (Leu), isoleucine (Ile), and valine (Val), have been found to have important mediating effects in protein synthesis, glucose homeostasis. Methods: This literature review aims to explain further the role of BCAAs in sarcopenia. Results: Numerous studies have demonstrated the advantages of BCAAs for maintaining or improving skeletal muscle mass and performance in both healthy elderly people and those with other comorbidities. It was also shown that resistance training and vitamin D supplementation enhanced the benefits of BCAAs. Conclusion: There are still study results that contradict the role of BCAAs in sarcopenia, hence more research with homogeneity in supplementation dosage and outcome measurement methods is required in order to obtain stronger evidence to support its claims.